Abamectin: an uncommon but potentially fatal cause of pesticide poisoning - Bansod, Y. V.; Kharkar, Sandeep V.; Raut, Arshish; Choudalwar, Piyush (International Journal of Research in Medical Sciences, 2017)
Human intoxication with abamectin is not frequently reported. It is an uncommon but potentially fatal cause of pesticide poisoning. In contrast to common organophosphate poisoning the toxic effects of avermectin in humans are not clearly defined. Ingestion of a large dose of avermectin may be associated with life-threatening complications. The therapy for avermectin poisoning is mainly symptomatic and supportive. The prognosis of patients with avermectin poisoning is likely to be favorable unless they are complicated by severe hypotension or aspiration. We hereby report a case with abamectin poisoning with neurological toxicity and respiratory failure which responded to supportive line of therapy.